2017
DOI: 10.1007/s10096-017-3053-1
|View full text |Cite
|
Sign up to set email alerts
|

Blastocystis in Côte d’Ivoire: molecular identification and epidemiological data

Abstract: Blastocystis is an enteric protozoan infecting humans and animals in both developed and developing countries at all latitudes. Despite this, data on Blastocystis infection are not available for several geographical areas, including many African countries. In this study, a survey was conducted on Blastocystis among humans and domestic animals in rural and urban localities in Côte d'Ivoire, in order to investigate the prevalence, the subtype distribution, and the zoonotic potential in association with sociodemog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
14
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 39 publications
6
14
2
Order By: Relevance
“…In this aim, only data obtained by molecular methods were recorded as non-molecular methods such as microscopic observation of fresh feces are known to greatly underestimate the prevalence of the parasite [ 39 , 41 ]. The prevalence of the parasite ranges between 25.6% and 100% depending on the geographical area [ 12 , 13 , 31 , 36 , 37 , 38 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. By focusing on the neighboring countries of Senegal (West Africa), the prevalence of Blastocystis sp.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this aim, only data obtained by molecular methods were recorded as non-molecular methods such as microscopic observation of fresh feces are known to greatly underestimate the prevalence of the parasite [ 39 , 41 ]. The prevalence of the parasite ranges between 25.6% and 100% depending on the geographical area [ 12 , 13 , 31 , 36 , 37 , 38 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. By focusing on the neighboring countries of Senegal (West Africa), the prevalence of Blastocystis sp.…”
Section: Discussionmentioning
confidence: 99%
“…By focusing on the neighboring countries of Senegal (West Africa), the prevalence of Blastocystis sp. was, respectively, 58.2% [ 38 ] and 70% [ 45 ] in two different surveys performed in Côte d’Ivoire and 49.7% in Mali [ 46 ]. Two other field studies showed a prevalence of 49% [ 31 ] and 84% [ 37 ] in Nigeria, while only one small-scale cohort screened in Liberia [ 31 ] indicated a frequency of the parasite of ~70%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…remain scarce. Similarly, molecular methods unveiled high genetic diversity of Blastocystis sp., the most common single-celled eukaryote in fecal samples of healthy humans [1219]: so far, 10 genetic subtypes (ST1–9 and ST12) have been found in humans, with ST3 being the most common [16]. Apart from Entamoeba and Blastocystis , other presumably non-pathogenic intestinal protozoa have been studied only exceptionally by molecular methods [1].…”
Section: Introductionmentioning
confidence: 99%